Fulvic acid complexation of Eu(III) and Cm(III) at elevated temperatures studied by time-resolved laser fluorescence spectroscopy - Fröhlich, Daniel R.; Skerencak-Frech, Andrej; Gast, Michael; Panak, Petra (Dalton transactions, 2014)
The interaction of Eu(III) and Cm(III) with three different aquatic fulvic acids (FA) was studied as a function of the temperature (T = 20-80 °C) in 0.1 M NaCl solution by time-resolved laser fluorescence spectroscopy. The speciation of both trivalent metal ions was determined by peak deconvolution of the recorded fluorescence spectra. For each studied metal ion-FA system only one complexed species is formed under the given experimental conditions. The stability constants at 20, 40, 60 and 80 °C (log β′(T)) were determined according to the charge neutralization model. The log β′ (20 °C) for the different FAs show similar values (log β(20 °C) = 5.60-6.29). The stability constants increase continuously with increasing temperature by approximately 0.3-1.0 orders of magnitude. The reaction enthalpies and entropies are derived from the integrated Van't Hoff equation. The results show that all investigated complexation reactions are endothermic and entropy-driven.